Synthesis , Spectroscopic and Antibacterial Studies of Zinc(II) Complexes Derived from Salicylaldehyde, Leucylalanine and Glycylglycine (Baghdad Science Journal, 2012)
Two Schiff base ligands L1 and L2 have been obtained by condensation of salicylaldehyde respectively with leucylalanine and glycylglycine then their complexes with Zn(II)were prepared and characterized by elemental analyses , conductivity measurement , IR and UV-Vis .The molar conductance measurement indicated that the Zn(II) complexes are 1:1 non-electrolytes. The IR data demonstrated that the tetradentate binding of the ligands L1 and L2 . The in vitro biological screening effect of the investigated compounds have been tested against the bacterial species Staphlococcus aureus, Escherichia coil , Klebsiella pneumaniae, Proteus vulgaris and Pseudomonas aeruginosa by the disc diffusion method . A comparative study of inhibition values of the Schiff base ligands and their complexes indicated that the complexes exhibit higher antimicrobial activity than the free ligands . Zinc ions are proven to be essential for the growth-inhibitor effect. The extent of inhibition appeared to be strongly dependent on the initial cell density and on the growth medium .